2014
DOI: 10.3109/17549507.2014.977348
|View full text |Cite
|
Sign up to set email alerts
|

The Autism Diagnostic Observation Schedule and narrative assessment: Evidence for specific narrative impairments in autism spectrum disorders

Abstract: The present findings provide evidence that children with ASD exhibit subtle story generation impairments and provide preliminary support for the inclusion of narratives elicited as part of the ADOS in the assessment of specific language skills in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 33 publications
9
65
2
Order By: Relevance
“…Compared to TD groups that are well‐matched for chronological age, nonverbal IQ and formal language (syntax or vocabulary), ASD groups usually underperform in the production of appropriately informative referring expressions during narrative tasks [Colle, Baron‐Cohen, Wheelwright, & van Der Lely, ; Suh et al, ; Banney, Harper‐Hill, & Arnott, ; Arnold, Bennetto, & Diehl, ]. The same has been found in production studies that have used interactive experimental manipulations of the participant and interlocutor's shared visual perspective [Nadig, Vivanti, & Ozonoff, ; Fukumura, ; Dahlgren & Dahlgren Sandberg, ; Volden, Mulcahy, & Holdgrafer, ; Nadig, Seth, & Sasson, ].…”
Section: Introductionmentioning
confidence: 83%
“…Compared to TD groups that are well‐matched for chronological age, nonverbal IQ and formal language (syntax or vocabulary), ASD groups usually underperform in the production of appropriately informative referring expressions during narrative tasks [Colle, Baron‐Cohen, Wheelwright, & van Der Lely, ; Suh et al, ; Banney, Harper‐Hill, & Arnott, ; Arnold, Bennetto, & Diehl, ]. The same has been found in production studies that have used interactive experimental manipulations of the participant and interlocutor's shared visual perspective [Nadig, Vivanti, & Ozonoff, ; Fukumura, ; Dahlgren & Dahlgren Sandberg, ; Volden, Mulcahy, & Holdgrafer, ; Nadig, Seth, & Sasson, ].…”
Section: Introductionmentioning
confidence: 83%
“…For instance, Colle et al () found that during narrative production, individuals with ASD used fewer personal pronouns and referential expressions, which require ToM abilities. Other studies reporting greater production of ambiguous pronouns in individuals with ASD compared to NT individuals (Baixauli et al, ; Banney et al, ; Norbury & Bishop, ; Novogrodsky, ; Suh et al, ) also suggest that some difficulties in narrative production may be related more to ToM abilities than to general linguistic skills.…”
Section: Additional Limitations Of the Visual Ease Assumptionmentioning
confidence: 94%
“…Studies using visual narratives as prompts in narrative elicitation tasks have overwhelmingly found impaired narrative production in both children and adults with ASD compared to NT individuals (see meta‐analysis in Baixauli, Colomer, Roselló, & Miranda, ). Such deficits include reduced syntactic complexity (Banney, Harper‐Hill, & Arnott, ; Capps, Losh, & Thurber, ; Norbury & Bishop, ); fewer pronominal references (Colle, Baron‐Cohen, Wheelwright, & Van der Lely, ; Rumpf, Kamp‐Becker, Becker, & Kauschke, ); greater use of ambiguous pronouns or references (Banney et al, ; Norbury & Bishop, ; Novogrodsky, ; Suh et al, ); fewer narrative elements (Banney et al, ); reduced references to internal or cognitive states (Baron‐Cohen, Leslie, & Frith, ; Capps et al, ; Rumpf et al, ); impairments in making inferences and understanding causal relationships between events (Losh & Capps, ); and, overall, stories that are less coherent and diminished in semantic quality (Diehl, Bennetto, & Young, ; Losh & Gordon, ; Rollins, ; Tager‐Flusberg, ). In contrast to these studies, Tager‐Flusberg and Sullivan () found no differences in narrative production abilities in participants with ASD compared to NT controls who were matched on linguistic ability.…”
Section: Tests Of the Visual Ease Assumptionmentioning
confidence: 99%
“…Even in high-functioning autism (HFA), where there has been no language delay or where language has reached normal levels by school age, language can remain affected when measured at the level of discourse, pragmatics, and higher-order semantics. Thus children with HFA without any language impairment as measured by standardized tests can show such impairment in a story generation task (Norbury et al 2014;Banney et al 2015). Even in people with a diagnosis of Asperger's, language can be abnormal behaviorally in prosody, volume, pragmatics, rate, and comprehension (Noterdaeme et al 2010) and be processed differently in the brain (Radulescu et al 2013;Moseley et al 2016).…”
Section: What Studies Of Language In Asd To Date Revealmentioning
confidence: 99%
“…In no subgroup on the autism spectrum was performance on 'that' worse than on 'the', as a pragmatic account would have predicted. Difficulties with anaphoric definite noun phrases and pronouns have been highlighted in several studies of narrative in ASD (Baltaxe and D'Angiola 1996;Banney et al 2015;Norbury, Gemmell and Paul 2013).…”
Section: What Studies Of Language In Asd To Date Revealmentioning
confidence: 99%